Ultrasonic Mammography with Circular Transducer Array - Krzysztof J. OPIELIŃSKI; Piotr PRUCHNICKI; Tadeusz GUDRA (Archives of Acoustics)
Ultrasonic projection imaging is similar to X-ray radiography. Nowadays, ultrasonic projection methods have been developed in the set-up of multi-element flat arrays with miniature transducers, where one of the array acts as a transmitter and the other one is a receiver.